The Anthem companion to Maurice Halbwachs - Leroux, Robert, 1964-; Marcel, Jean-Christophe (Anthem companions to sociology., 2021)
This book seeks to place Halbwachs in his historical and intellectual context, showing that his work was sensitive to the events of his time, and that the development of his analysis could be influenced by happenstance. The book does this, not by summarizing or synthesizing his thinking, by the growing literature embodied by many sociologists and historians of social sciences, published for the most part in scientific journals, that focus on the sociological thought that Halbwachs developed in his writings. Then come many studies that emerge from the history of ideas and epistemology: these are entirely devoted to a particular facet of Halbwachs' work, either to place it in its scientific context or to discuss it on the basis of fundamental cognitive issues.